PRODUKSI FILM DOKUMENTER "ALI PON: SANG MAESTRO" (FILM DOKUMENTER TENTANG BIOGRAFI MAESTRO SENI TRADISI BERPANTUN DI KOTA TANJUNGPINANG) - Fauzan Anangga; Kharisma Nasionalita (Dialektika, 2019)
This final work is taken the form of documentary film and aims to tell the beginning of Ali Pon’s journey to become a Maestro of Traditional Art. The work is created based on the theory of cultural communication, cultural inheritence, documentary film, cinematography, art of lighting and art of sound. The data collection for this final work uses the techniques of preliminary research, interview and literature study. The documentary begins with the story of the fondness he has for Pantun since his childhood. This eventually made him become a Pantun artist whose expertise is recognized by Ministry of Education and Culture, which ultimately inaugurated him into a Maestro of Traditional Art. With the inauguration, the Ministry hope that Ali Pon could contribute in Pantun culture inheritence. The conclusion of this final work is Ali Pon’s fondness for Pantun makes Ministry of Education and Culture recognized his expertise in the field and inaugurated him into a Maestro of Traditional Art, Pantun, in Tanjungpinang City.